PENERAPAN PENDEKATAN DIFFERENTIATED INSTRUCTION UNTUK MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA - Iskandar, Ratu Sarah Fauziah (AlphaMath : Journal of Mathematics Education, 2017)
Mathematical problem solving ability must be owned by students in learning mathematics. This research is motivated lack of mathematical problem solving ability of students. To overcome this, it is necessary to improve their lessons. In this research, Differentiated Instruction approach is applied to students prepared for being mathematics teachers. This study aims to improve problem solving skills of students through the approach of Differentiated Instruction. This research is Non-equivalent Control Group Design. With a population of all students Muhammadiyah University of Tangerang. The samples consist of two class from 5th grade students of mathematics educational departement. The data collecting uses instrument in the form of test about the ability of mathematical problem solving. The result of this research indicates that the applying of Differentiated Instruction approach is significant influencing the increase of the mathematical problem solving ability.Keyword: Differentiated Instruction Approach, Mathematical Problem Solving Ability